The Role of Fruit Waste-Based Briquette Sales in Enhancing Income and Community Welfare in Babussalam Village - M Alkadri Perdana; Johny Custer; Andri Nofiar Am; Lukman Hakim Nasution; Wahyu Triyono; Siti Rahayu (Economic: Journal Economic and Business, 2025)
This study analyzes the role of fruit waste briquette sales in increasing income and community welfare in Babussalam Village. Fruit waste, which is usually discarded, can be converted into environmentally friendly briquettes with economic value. The study used a descriptive quantitative approach with a case study, involving 30 respondents consisting of briquette producers and distributors. Data were collected through observation, interviews, and questionnaires, then analyzed using descriptive statistics and simple regression. The results show that briquette sales significantly increased household income by an average of 35% and improved welfare indicators such as education, health, and household consumption. The study concludes that the utilization and commercialization of fruit waste briquettes supports economic improvement in rural communities while simultaneously promoting sustainable environmental management. Further research is recommended to expand market access and integrate digital marketing strategies to increase the competitiveness of environmentally friendly briquette products.